An equity framework for family, community, and school partnerships. Issue 1 (2nd January 2021) - Teemant, Annela; Borgioli Yoder, Gina; Sherman, Brandon J.; Santamaría Graff, Cristina
ABSTRACT: Equity has often been identified as a foundational concept for truly inclusive and reciprocal partnerships among schools, families, and communities. Equity can be difficult for schools to achieve without cultivating new paradigms for interacting with historically marginalized students, families, and communities. In order to bridge the ideal of equity with radical, scalable, and sustainable institutional change, we developed an equity framework for cultivating mutual interdependence among families, communities, and schools in partnership. Rooted in sociocultural and critical theories, this framework builds upon the values of mutual respect, democratic participation, critical consciousness, and sustainability. These values then support cycles of collaborative action amongst stakeholders leveraging problem posing and community organizing to address inequities. In our article, we discuss the underlying theory supporting the framework and elaborate upon its implications for practice.